Mobile health apps to reduce sedentary behavior: a scoping review - Ueno, Deisy Terumi [UNESP]; Guerra, Paulo Henrique; Messetti Christofoletti, Ana Elisa [UNESP]; Bonolo, Angelica [UNESP]; Nakamura, Priscila Missaki [UNESP]; Kokubun, Eduardo [UNESP] (Oxford Univ Press, 2021)
Given the continued increase in mobile health applications (apps) aimed at healthcare and the recognition of sedentary behavior (SB) as a public health problem, the goal of this scoping review study was to summarize the effects of interventions based on mobile health apps designed to reduce SB in adults, with a specific focus on SB. The electronic databases PubMed, PsycINFO, SportDISCUS, Web of Science, and manual searches in reference lists were conducted on papers published up to September 2020. Nine out of the 897 studies researched were included and composed the descriptive synthesis. The investigations found in the present study showed a decrease in time spent on television viewing and in total time spent sitting, as well as an increase in the number of SB breaks after interventions based on mobile health apps. In conclusion, despite the growing interest in intervention programs in SB, only nine studies have used smartphone apps as a strategy to reduce SB in adults. Mobile health apps were proved to be effective in SB reduction, as assessed by different parameters, and should be encouraged. However, further studies are needed to verify the long-term effects of the utilization of such applications.
Keywords: sedentary behavior; applications; mobile health; smartphone; review